“Tegodek-Godek dait Tetuntel-Tuntel”: Development of Digital Books to Strengthen Character Education for Elementary School Children - Nisha Ayu Dwi Sukazi; Khairun Nisa; Prayogi Dwina Angga (Journal of General Education and Humanities, 2025)
The limited media of pictorial reading that raises local wisdom and the lack of application of character values in learning are problems that underlie the need to develop relevant and contextual media for students. This research and development aims to develop a digital folklore book of the Sasak tribe, "Tegodek-Godek dait Tetuntel-Tuntel," with good validity and practicality and is useful as a means of strengthening character values for students. This research is a type of Research and Development (R&D) research with a 4D model approach. This research was carried out at SDN 14 Cakranegara and involved 33 students in grade V. The instruments used in this study were a validation questionnaire for media experts and subject matter experts, as well as a questionnaire for student and teacher responses as product users. The digital folklore book "Tegodek-Godek dait Tetuntel-Tuntel" as a whole has been declared very valid and very practical by validators and respondents. The results of the study showed that the results of the media validation test obtained a percentage of 100% (very valid); the validation of material experts reached 96.66% (very valid); student response results of 89.62% (very practical); and the teacher's response results were 97.5% (very practical). Thus, the existence of digital storybooks based on local wisdom can be used as an alternative learning media that is contextual to strengthen character education in elementary schools, as well as to encourage the development of similar media in other cultural areas.